2014
DOI: 10.1101/gr.162412.113
|View full text |Cite
|
Sign up to set email alerts
|

Genome methylation in D. melanogaster is found at specific short motifs and is independent of DNMT2 activity

Abstract: Cytosine methylation in the genome of Drosophila melanogaster has been elusive and controversial: Its location and function have not been established. We have used a novel and highly sensitive genomewide cytosine methylation assay to detect and map genome methylation in stage 5 Drosophila embryos. The methylation we observe with this method is highly localized and strand asymmetrical, limited to regions covering ∼1% of the genome, dynamic in early embryogenesis, and concentrated in specific 5-base sequence mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
121
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 33 publications
(74 reference statements)
8
121
0
1
Order By: Relevance
“…For ease of interpreting results, we analyzed hmrC in Drosophila melanogaster because (i) cytosine methylation in Drosophila DNA is either absent or very low, being restricted to specific cellular contexts (6,7), and (ii) we have found no evidence of DNA hydroxymethylation in this organism ( fig. S1).…”
mentioning
confidence: 99%
“…For ease of interpreting results, we analyzed hmrC in Drosophila melanogaster because (i) cytosine methylation in Drosophila DNA is either absent or very low, being restricted to specific cellular contexts (6,7), and (ii) we have found no evidence of DNA hydroxymethylation in this organism ( fig. S1).…”
mentioning
confidence: 99%
“…Recently LC-MS/MS and the immuno-precipitation prior to bisulphite conversion studies have reported the presence of DNA methylation in D. melanogaster genome 19,20 . Substantial evidence suggests that immunoaffinity based methods could find application in detecting DNA methylation in D. melanogaster 27,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The genome-wide DNA methylation maps of insects like Drosophila melanogaster 9 , Bombyx mori 11 , Solenopsis invicta 12 and Apis mellifera 13,14 have been generated using whole genome bisulphite sequencing. Therefore it is important to study whether these methylation signatures play an important role in life cycle processes in invertebrates.Though Drosophila lacks the canonical DNMT1, DNMT3A and DNMT3B, the presence of very low levels of DNA methylation has been reported in D. melanogaster [15][16][17][18][19][20][21][22] . Presence of methylated DNA has been a controversial issue since few reports suggest that D. melanogaster lacks DNA methylation and DNMT2 is indeed an RNA methyltransferase that uses a DNA methyltransferase type of mechanism [23][24][25] .…”
mentioning
confidence: 99%
See 2 more Smart Citations